ANALISIS LOYALITAS WISATAWAN DI DESA WISATA PENGLIPURAN MELALUI COMMUNITY BASED TOURISM DAN KEPUASAN - Yasa, I Made Buda; Dewi, Nyoman Diah Utari (Jurnal Ilmiah Global Education, 2023)
This research is motivated by the existence of numerous tourism villages that are designed as tourist destinations but have not been able to operate according to plan. Penglipuran Village, which currently operates as a popular tourist village, serves as an inspiration to be used as a research model. This study aims to analyze variables that can serve as predictors of tourist loyalty to visiting a tourist village. The research involves 50 respondents selected through the accidental sampling method. Data collection is conducted using a questionnaire. The data analysis technique employs multiple linear regression analysis with the SmartPLS application. The research findings indicate that tourist satisfaction and community-based tourism (CBT) have a positive influence on tourist loyalty. Tourist satisfaction is represented by accessibility, while CBT is represented by community participation. Tourist satisfaction stands out as the dominant variable capable of predicting the loyalty of tourists who visit the tourist village.